Sootnoshenie bneledovykh sredstv OFP i SFP na etape nachalnogo obucheniya parnomu kataniyu - Pozdnyakov, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
A study had been carried out to get information about teaching beginners in figure skating (couples). The results of the investigations showed that the general kind of training at the beginners' level should have priority, the optimal relation between general and specific trainng should be about 60/65% : 40/35%.